2021
DOI: 10.29278/azd.907047
|View full text |Cite
|
Sign up to set email alerts
|

Ordu ili koyunculuk işletmelerinde görülen önemli hastalıkların ve sorunların belirlenmesi

Abstract: Bu araştırmada, Ordu ilindeki koyunculuk işletmelerinde görülen hastalıkların ve önemli sorunların belirlenmesi amaçlanmıştır. Araştırmada, en az 80 baş sürü büyüklüğüne sahip işletmeler dikkate alınmıştır. İşletmelerin belirlenmesinde rastgele seçim yöntemi kullanılmış ve toplam 86 işletmede yüz yüze anket çalışması yapılmıştır. İşletme sahiplerinin %30.23’ünün 25-40 yaş, %34.88’inin 41-55 yaş arasında ve 56 yaşından büyük olan işletme sahiplerinin oranının ise %34.88 olduğu saptanmıştır. Yine, işletme sahipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Distribution in Turkey.—Diyarbakır, Elâzığ, Malatya, Tunceli (Alkan 1947); Ankara (Alkan 1952); Ankara, Eskişehir, Konya, Niğde (Karaca 1956); Çukurova region (Düzgüneş 1977); Erzurum-Narman, Tortum, Oltu, İspir, Erzincan-merkez, Kemaliye, Kars-Kağızman (Alaoğlu 1984); Aydın, Çanakkale, Denizli, İzmir, Kütahya, (Önuçar and Ulu 1993); the area of Van Lake Basin, Ankara, Izmir; Van Lake Basin, Yalova (Denizhan and Çobanoğlu 2010, Denizhan 2018, Denizhan and Erdoğan 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Distribution in Turkey.—Diyarbakır, Elâzığ, Malatya, Tunceli (Alkan 1947); Ankara (Alkan 1952); Ankara, Eskişehir, Konya, Niğde (Karaca 1956); Çukurova region (Düzgüneş 1977); Erzurum-Narman, Tortum, Oltu, İspir, Erzincan-merkez, Kemaliye, Kars-Kağızman (Alaoğlu 1984); Aydın, Çanakkale, Denizli, İzmir, Kütahya, (Önuçar and Ulu 1993); the area of Van Lake Basin, Ankara, Izmir; Van Lake Basin, Yalova (Denizhan and Çobanoğlu 2010, Denizhan 2018, Denizhan and Erdoğan 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Size and rate of infected area Sunn pest, whose presence has been known in Central Anatolia since 1942 (Alkan 1942), became a problem for the first time in wheat cultivation areas in Ankara, Burdur and Isparta in 1988 when its population density reached levels that required control, and each year showed different levels of prevalence up to day (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In similar survey studies, it was reported that at least 3% (Yamane, 2010) or 10% (Sümbüloğlu and Sümbüloğlu, 2000) of the population would be sufficient to determine the sample size. In this study, the number of sample enterprises to be surveyed was calculated using the following formula within 10% sampling error and 95% reliability limits (Alkan and Türkmen, 2020;Alkan and Türkmen, 2021;Çiçek and Erkan, 1996;Satar et al, 2022). n= N.t 2 .p.q / d 2 .…”
Section: Methodsmentioning
confidence: 99%